2013
DOI: 10.1007/s00360-013-0775-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal stress physiology and body condition differ among co-occurring tropical finch species

Abstract: Seasonal changes in avian hormonal stress responses and condition are well known for common species found at temperate and arctic latitudes, but declining and tropical species are poorly studied. This study compares stress and condition measures of co-occurring declining and non-declining tropical grass finch species in Australia. We monitored declining Gouldian finches (Erythrura gouldiae) and non-declining long-tailed and masked finches (Poepila acuticauda and P. personata) during two seasons that are potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…This reduction is probably insufficient to limit breeding finches at the start of the dry season when seeds are still abundant at the soil surface (Weier et al 2018). However, a reduction from median seed densities of 800 seeds m −2 down to 600 seeds m −2 may constitute a limiting factor for Gouldian finches in the late dry season when finches are under increasing stress (Maute et al 2013, Legge et al 2015 and seeds at the soil surface are increasingly sparse (Weier et al 2018). Although previous research has shown that combined bird and mammal seed predation has negligible impacts on S. intrans seed numbers in Northern Territory savannas, harvester ants of the genus Meranoplus, Smith 1854, species can deplete Sorghum spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction is probably insufficient to limit breeding finches at the start of the dry season when seeds are still abundant at the soil surface (Weier et al 2018). However, a reduction from median seed densities of 800 seeds m −2 down to 600 seeds m −2 may constitute a limiting factor for Gouldian finches in the late dry season when finches are under increasing stress (Maute et al 2013, Legge et al 2015 and seeds at the soil surface are increasingly sparse (Weier et al 2018). Although previous research has shown that combined bird and mammal seed predation has negligible impacts on S. intrans seed numbers in Northern Territory savannas, harvester ants of the genus Meranoplus, Smith 1854, species can deplete Sorghum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Patchy early dry season fires may also allow for greater development of mature, seeding perennial grasses as wet season seed resources for finches (Dostine et al 2001). Previous studies have highlighted food shortages of perennial grass seeds under frequent fire regimes, especially during the late dry and the wet seasons (Dostine et al 2001, Maute et al 2013, Legge et al 2015, although this is yet to be explicitly demonstrated. Future work into finch spatial movements and landscape resource use during putative food shortage periods will be necessary to fully unravel key ecological limitations for this tiny threatened grass finch.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low average body condition of individuals in one habitat or year relative to another could indicate poorer habitat quality or environmental conditions. Additionally, glucocorticoids can mediate foraging behavior (Astheimer et al, ) and are sometimes inversely linked to body condition (Kitaysky et al, ; Moore et al, ; Hews and Baniki, ; Maute et al, ), so high glucocorticoid levels found in concert with low body condition can be interpreted as potential evidence for poor habitat quality.…”
Section: Introductionmentioning
confidence: 99%
“…Blood was drawn by puncturing the brachial vein with a 26-gauge needle and collecting a sample volume of <60μL with a capillary tube. Samples taken for the purposes of genetics and were bled immediately after capture, those taken for hormone analysis were taken between 5 and 60 minutes after capture [21]. The birds were restrained using ringers grip, no anaesthetics were administered as the bleeding procedure takes less than two minutes per bird.…”
Section: Methodsmentioning
confidence: 99%